An accelerated life test model for solid lubricated bearings used in space based on time-varying dependence analysis of different failure modes. (November 2018) - Zhang, Chao; Pan, Lingfeng; Wang, Shaoping; Wang, Xingjian; Tomovic, Mileta
Abstract: Solid lubricated bearings are crucial mechanical components of spacecraft, and their failures are risky to the integrity of the spacecraft. To assess the reliability measures of solid lubricated bearings, accelerated life tests (ALT) have to be conducted. This paper proposes an ALT model of solid lubricated bearings. Firstly, the reliability function of solid lubricated bearings for each failure mode is derived based on Weibull distribution, and the effect of acceleration stresses is described by the generalized Eyring model. The time-varying copula function is then used to characterize the dependence between the two failure modes and further derive the reliability functions under normal and accelerated conditions. The unknown parameters in this proposed ALT model are estimated via the Bayesian approach. The proposed model is validated by the data collected from an ALT of solid lubricated bearings, and the results show that this model is accurate and effective. Highlights: We build an accelerated life test model for solid lubricated bearings. The reliability function for each failure mode is derived and effect of acceleration stresses is considered. Dependence of different failure modes is described by time-varying Frank copula function. Copula function with quadratic function to describe time-varying effect has the most accurate result.